Razvoj plinskega odvodnika - Pregelj, Andrej (Vakuumist, 2002)
Each overvoltage stroke in electric network can cause damage in the surrunding highly sensitive electronic devices. To protect these devices several overvoltage arresters are used (mounted in connecting electric lockers in buildings) and among them the gas filled arresters are the most important. These are hermetically closed cells in which argon or its mixture with another noble gas is captured between housing and isolated electrode. At defined conditions (tension stroke etc.) it becomes ionised - i. e. capable to conduct the electric current. The gas arrester for higher powers which is developed in our laboratory , is connected with other electro-elements in a special device which acts protectively in such a manner that it leads off the lighting surge into fround. Construction of the cell is relatively simple; eight or nine components are joined together by advanced technological procedure. The manufacturing receipt has to assure the demand properties such as vacuum tightness, sparkove voltage, insulation resistance energy fitness, repetitveness etc. Besides measurements of mentioned characteristics a short description of technology development until presen state and some experiments are presented.
Keywords: prenapetostna zaščita; plinski odvodniki; prenapetnostni odvodnik